2006
DOI: 10.1348/147608305x52676
|View full text |Cite
|
Sign up to set email alerts
|

Family and coping factors in the differentiation of childhood anxiety and depression

Abstract: The purpose of this investigation was to explore whether specific contextual (perception of family relationships) and personal (coping strategies) factors are more likely to be associated with anxiety or depression. The research was conducted on a sample of 331 children and adolescents ranging in age from 10 to 16 years who completed measures of the anxiety symptoms, depressive symptoms, coping strategies, and family interactions. Data were analysed according to gender differences. Among family variables, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
3
12
0
1
Order By: Relevance
“…Though few studies are available on the specific effects of family variables on anxiety and depression, findings indicate that specific parenting domains (e.g. rejection) are stronger associated with depression than with anxiety [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Though few studies are available on the specific effects of family variables on anxiety and depression, findings indicate that specific parenting domains (e.g. rejection) are stronger associated with depression than with anxiety [44]. …”
Section: Discussionmentioning
confidence: 99%
“…Other evidence suggests that active coping strategies are negatively related to mental health problems such as depression and anxiety (Eisenberg et al, 1995;Losoya, Eisenberg, & Fabes, 1998). Conversely, some findings also suggest positive relationships between the active coping methods and anxiety in school-age in Croatian children (Vulic-Prtoric & Macuka, 2006) and Dutch children (Muris et al, 1998). A predictive relationship was found between active coping and lower anxiety in school-age Swedish children (Larsson et al, 2000), whereas other studies have not found any significant associations (Lengua & Long, 2002;Sandler, Tein, et al, 2000;Sheffield Morris & Ricard Age, 2009).…”
Section: Coping and Anxiety Symptomsmentioning
confidence: 92%
“…For example, while theories generally suggest that active coping is associated with fewer psychological difficulties (Aldwin, 2007), empirical research has found evidence of active coping strategies being both positively (e.g., Muris et al, 1998;Smith et al, 2006;Vulic-Prtoric & Macuka, 2006) and negatively (e.g., Eisenberg et al, 1995;Sandler, Tein, & West, 1994) related to mental health difficulties, such as anxiety in children. Positive relationships have generally been found with support seeking coping strategies and childhood anxiety symptoms (Larsson et al, 2000;Muris et al, 1998;Smith et al, 2006;Vierhaus & Lohaus, 2009;Vulic-Prtoric & Macuka, 2006), despite theories suggesting the opposite. The studies that have investigated the relationships between avoidance and distraction coping and childhood anxiety symptoms have discovered positive relationships (e.g., Larsson et al, 2000;Sheffield Morris & Ricard Age, 2009).…”
Section: Childhood Anxiety Symptoms Coping Strategies and Coping Efmentioning
confidence: 99%
See 2 more Smart Citations